Environmental journalism - Sudhir, S.N (Pearl Books, 2021)
Environmental journalism is yet to develop as a full-fledged field within journalism. There are hundreds of stories waiting to be done, but not enough reporters who take the trouble to work on them in depth. But environment and wildlife issues are gradually gaining some prominence in the press and some stories are even making it to the front page or main news desk. A degree/diploma in science and a course in journalism or science communication from a good institute would be a prerequisite to work with newspapers/broadcast media. A background in environmental issues and related laws (possibly through a degree in environmental science or through additional diploma courses) would be beneficial. The goal of the reporter's privilege, like the attorney/client like the doctor/client privileges, is to increase the flow of information in circumstances in which society wishes to encourage open communication. The reporter's privilege seeks to protect the flow of information into the public discourse. Today, coverage of the environment is not only reporting current practices, issues and trends but what kind of repercussions they will have, in the social and political realm. The difficulties in reporting on the environment involve uncertainties associated with research and innovation, and their long-term, real-life impacts.